Determination of Effectiveness Absorption of The Rice Husk And Hazelnut Shell to Purification Used Cooking Oil - Loth Botahala; Yanti Malailak; Herlin Silvia Maure; Hagar Karlani (Hasanuddin University, 2019)
The effectiveness of the absorption of activated rice husk and hazelnut shells on the purification of used cooking oil has been carried out. The aim is to determine the absorption capacity of the active charcoal of rice husk and hazelnut shells to purify used cooking oil. After being physically activated, activated charcoal from rice husk and pecan shells is applied to the purification of used cooking oil. The results show that the quality of hazelnut shell charcoal is better than rice husk after it is applied to purifying used cooking oil.